Brooding over Integration of Skills in ELT Lessons: Reasons and Remedies: Exploring the Challenges and Solutions in Integrating Skills in ELT Lessons (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Integration of skills approach has been gained the momentum in English language teachingsince the 1980s. Growing demand for communicative competence of the graduate in the job market gavean impetus for the call for integrated skill approach. Effective integration of skill can bring better resultsin achieving learning outcome of the courses delivered in ELTESLEFL settings too. Many scholarsspoke about the effectiveness integration of skills. According to Jing (2006), integrated method is widelydiscussed and recognized as the best mean for the development of communicative competence. Thispertains the ever-widening need of a learner to be involved in a process meeting real life challenges ofusing a foreign language. He substantiates his argument by saying that multiple skills are used forcommunication in day- to-day life. To achieve this objective, integration of language skills will be mostreliable instructional method to take learners to the higher levels of communicative ability in thelanguage. The motto ‘English for life’ is not achieved though there are many English language courseswhich are tailor made for this. There are many factors that contributed to this issue. Therefore, a carefulstudy about the issue will be timely and worth conducting to shed light to the cardinal issues that prevailin the sector. This paper is based on the study conducted among the lecturers and students ofPreparatory Studies Program (PSP), a foundation study program for the undergraduate, at Englishlanguage Centre of the Ibra branch of University of Technology and Applied Science (UTAS)-Oman. Thepaper propounds remedies on the vital challenges.